Effects of exercise preconditioning on the levels of interleukin-6 and 10 of Myocardial in mice with breast cancer - Z Ebrahimpur; M peeri; H Matin Homaee; p farzanegi (فصلنامه ابن سینا)
Background: There is a high risk of mortality from cardiovascular diseases among women with breast cancer. Aerobic exercise training is effective in preventing and survival of these diseases as well as prevention and treatment of breast cancer. This study aimed to investigate the effects of exercise preconditioning on the levels of interleukin 6 (IL-6) and 10 (IL-10) in cardiac tissue in mice with breast cancer.